CYBER SECURITY POWER RANKING BY COUNTRY AND ITS IMPORTANCE ON WORLD POLITICS - Barış ÇELİKTAŞ (Fırat University, 2019)
Today, the rapid development of information communication systems and technologies has added the area of cyber space in the field of land, sea, air and space operations, and all other operation areas have become to move in cyber space. Cyber space has begun to be regarded as the fifth dimension of the battlefield by the strong, effective countries and the armed forces of the world. Thus, cyber space has become an important deterrent force on the battlefield, as well as being one of the main means of determining the internal or external policies of countries in the 21st century. Today, countries strive to be in a favorable position in the cyber space and im-prove their influence by enhancing technological adequacy and capabilities. Countries which are too dependent on technology and internet can be exposed to cyber attacks more over the internet, an indispensable element of cyber attacks. These cyber attacks usually target the critical infrastructure sectors such as transportation, electric, educa-tion, health, nuclear facilities, agriculture, industry, energy, water, finance, and tele-communications, which one of utmost importance for the countries. It is not hard to imagine the possibility of immense financial losses, loss of life and property and drastic reductions in services that can be experienced if such attacks occur. In this study, as a result of compiling statistical studies done by research com-panies and open source data on the internet, some world countries’ Cyber Security Power Ranking will be tried to establish by using their cyber defense power, cyber attack power, as well as the dependence on the cyber space. As well as the G8 countries formed by the highest Gross National Product (GNP), the countries such as India, South Korea, North Korea, Israel, Iran, Brazil, and Turkey among that have recently occupied significant space in cyber space will be used. Consequently, as a result of the Cyber Security Power Ranking will be tried to determine countries’ position in the world and will be had a preliminary knowledge of the countries and the national cyber security awareness level will be tried to be in-creased. In addition, considering that the components that affect the Cyber Security Power Ranking determine the power of cyber space in the countries, international organizations and countries will set up the cyber security policy and action plans for survival measures in this direction and also emphasize the importance of completing preparations for a hybrid war that will take place in the future.